EFFECT OF QUALITY OF WORK LIFE, JOB SATISFACTION, AND LEADERSHIP STYLE ON ORGANIZATIONAL COMMITMENT ON EMPLOYEES OF PT. TUNAS JAYA CIPTA MEDAN - Sinurat, Siti Normi (ITScience (Information Technology and Science), 2022)
In this modern era, companies need superior resources in order to achieve company goals. Companies need strong internal resources and can face all the challenges and changing times. The study aimed to determine the influence of Quality of Work Life, Job Satisfaction, and Leadership Style on Organizational Commitment to Employees of PT. Tunas Jaya Cipta Medan. This study took the population of all employees at PT. Tunas Jaya Cipta Medan had as many as 35 people. The sampling technique applied a saturated sample, meaning that the entire population was sampled. This study concluded that work life, job satisfaction, and leadership style significantly influence organizational commitment. This is indicated by the value of F-count (13.4) > F-table (2.87) with a significance level of 0.00 < 0.05. Suggestions for PT. Tunas Cipta Jaya Medan provides a good leadership style to provide job satisfaction in the company so that commitment is getting better and increasing. Then for the Quality of Work Life to be formed in such a way as one of the achievements of organizational commitment to be more capable and reliable.